Workload and Employee Performance in the Plantation Industry in Indonesia - Puspa Liza Ghazali; Dedi Iskamto; Asyraf Aftanorhan (Husnayain Business Review, 2023)
This study aims to determine the effect of workload on employee performance at PT. Perkebunan Nusantara V Administrative Division of Human Resources/General Sei Galuh Gardens. The population in this study were employees of the Human Resources/General Administration Section, namely as many as 50 people. In this study, researchers took all employees, namely 50 people. To get a sample of this study researchers used the census method. For data analysis and hypothesis testing using SPSS version 25. Hypothesis testing was carried out to determine the relationship between the independent variable and the dependent variable. The results of the hypothesis show that workload has an effect on employee performance. The determinant test shows that the R Squere value is 90.2%, meaning that there is an effect of workload on employee performance, while the remaining 9.8% is influenced by other variables outside of this research.